Atypical imaging presentation of hepatocellular carcinoma - Case series - Divya S,; Geetha G,; Ashwin Kumar A, (Asian Journal of Medical Sciences, 2025)
Hepatocellular carcinoma (HCC), the most common primary liver tumor, significantly contributes to cancer-related mortality worldwide. This case series investigated HCC imaging presentations, including portal vein tumor thrombus, multifocal HCC, cirrhotomimetic diffuse infiltrative HCC, metastasis to various organs, HCC with capsular rupture and hemoperitoneum, and unusual features like a fatty metamorphosis. Imaging plays a crucial role in HCC detection, diagnosis, staging, and posttreatment monitoring, and ultrasonography is recommended for screening and triple-phase computed tomography, which is essential for characterization and staging. Typical imaging features include arterial phase hyperenhancement, washout in later phases, and tumor capsule. Recognizing imaging presentations is vital for accurate diagnosis and management, as HCC complications indicate advanced disease and poor prognosis. This series highlights HCC’s diverse imaging spectrum of HCC and emphasizes the importance of identifying atypical presentations for timely diagnosis and appropriate management.